Estimating long-term global supply costs for low-carbon hydrogen - Gregor Brändle; Max Schönfisch; Simon Schulte (Institute of Energy Economics at the University of Cologne (EWI), 2020)
As part of the decarbonisation of the global economy, low-carbon hydrogen is expected to play acentral role in future energy systems. This article presents a comprehensive approach for estimating thedevelopment of global production and supply costs of low-carbon hydrogen from renewable energy sources(RES) and natural gas until 2050.For hydrogen from RES, globally distributed wind and solar photovoltaics (PV) potentials are taken asinputs for low or high temperature electrolysers. A linear optimisation model minimises hydrogenproduction costs by determining optimal capacity ratios for each RES and electrolyser combination, basedon hourly RES electricity generation profiles. For low-carbon hydrogen from natural gas, natural gasreforming with carbon capture and storage (CCS) and pyrolysis are considered. In addition to productioncosts, this analysis assesses the costs associated with the transportation of hydrogen by ship or pipeline.The combination of production and transportation costs yields a ranking of cost-optimal supply sources forindividual countries.Estimation results suggest that natural gas reforming with CCS will be the most cost-efficient low-carbonhydrogen production pathway in the medium term (2020-2030). Production of hydrogen from RES couldbecome competitive in the long run (2030-2050) if capital costs decrease significantly. Optimal long-termhydrogen supply routes depend on regional characteristics, such as RES conditions and gas prices. Importsare cost-effective where domestic production potential is small and/or cost-intensive. Additionally, goodimport conditions exist for countries which are connected to prospective low-cost exporters via existingnatural gas pipelines that can be retrofitted to transport hydrogen. Due to high costs for seabornetransport, hydrogen trade will most likely be concentrated regionally, and markets with different provisionschemes could emerge. The results are highly sensitive to capital cost assumptions and natural gas prices.
Keywords: Q40; Q42; Q49; 330; Low-Carbon Hydrogen; Hydrogen Production; Hydrogen Transportation; Levelised Cost